The Effect of Sugar Consentration and the Fermentation Time of Kombucha - Marni Otace Wulan Napitupulu; Setyohadi Setyohadi; Linda Masniary Lubis (Universitas Sumatera Utara, 2015)
The study was conducted to determine the effect of variations in sugar concentration and fermentation time on the quality of kombucha coffee. This study is one of the first steps to get a product that is more healthful from coffee. This research was conducted in July 2013 in the Laboratory of Food Technology, Faculty of Agriculture, USU, Medan, using a completely randomized design with two factors, namely variations in the concentration of sugar (G): (2, 4, 6, and 8%) and fermentation time (L): (5, 7, 9, and 11 days). The parameters analyzed were tannin content (%), pH, total soluable solid (oBrix), total microbial (x108 CFU/g), total acid (%), and organoleptic (color, aroma, and flavor). The results showed that variations in the concentration of sugar gave a significant effect on levels of tannin, pH, total soluble solids (TSS), total microbial (x108 CFU/g), and organoleptic taste, smell and color. Fermentation time gave a highly significant effect on levels of tannin, pH, total soluble solids (TSS), total microbial (x108 CFU/g),and organoleptic taste, smell and color. Interactions of the two factors had highly significant effect on levels of tannin, pH, total soluble solids (TSS), total microbial (x108 CFU/g), total acid (%), and organoleptic taste and smell. The best result was coffee kombucha with 8% sugar concentration and fermentation time of 5 days. Keywords: Fermentation time, kombucha coffee, sugar concentration